Biochar addition reduces salinity in salt-affected soils with no impact on soil pH: A meta-analysis - Wang, Xiao; Ding, Jianli; Han, Lijing; Tan, Jiao; Ge, Xiangyu; Nan, Qiong (Geoderma, 2024)
•Biochar can alleviate soil salinity stress.•Biochar amendment does not modify the soil pH in salt-affected soils.•Biochar increases cation exchange capacity by 17.0% in salt-affected soils.•The impact of biochar addition on ECe depends on biochar feedstock and soil initial salinization level. Salinization remains a major issue in soil degradation, for which biochar is a potential solution. In this meta-analysis, using 660 paired observations from 99 peer-reviewed articles, we evaluated biochar's effect on salt-affected soils and identified the initial soil properties, biochar properties and experimental factors influencing its efficacy. The results showed that the addition of biochar had a significant ameliorating effect on salt-affected soils. The soil electrical conductivity of saturated paste extract (ECe) was significantly reduced by 13.2%, and such effect was significant in severe salinization soil (rather than slight and moderate salinization). Meanwhile, the soil cation exchange capacity was significantly increased by 17.0%. However, the addition of biochar had no significant impact on soil pH. Model selection analyses further indicated that the level of initial salinity and the type of biochar feedstock were the most important factors regulating the response of soil ECe to biochar addition. In summary, while our study highlights the potential of biochar in ameliorating salt-affected soils, particularly in severely salinized soils, it also underscores the need for more comprehensive research in this field. Additional research is necessary to comprehensively address the significant heterogeneity of biochars, including their thorough characterization. In addition, more studies are required to explore the impact of biochar on both salt-tolerant and non-salt-tolerant plants in salt-affected soils.